Integrated Geological and Aeromagnetic Investigation of Barite Mineralization in Didango Area, Muri-Lau Sub-Basin Upper Benue Trough NE Nigeria - Hamman, Ishaku Kamale; Joseph, Clement Akan; Zakari, Mohammed (FUDMA JOURNAL OF SCIENCES, 2025)
Barite (BaSO4) is a critical industrial mineral primarily used as a weighting agent in drilling fluids for oil and gas exploration due to its high specific gravity and chemical inertness. Despite the abundance of barite mineralization in Nigeria, many deposits in the Upper Benue Trough, particularly within the Muri-Lau Sub-Basin, remain poorly studied and their structural controls inadequately understood. This study integrates detailed geological mapping and high-resolution aeromagnetic analysis to investigate the mode of occurrence, structural controls, and economic potential of barite mineralization in the Didango area. Field observations revealed that barite occurs in hydrothermal veins associated with fault zones and fractures within sedimentary rocks. Aeromagnetic data, including Total Magnetic Intensity (TMI), Analytical Signal, Source Parameter Imaging (SPI), and Vertical Derivative maps, highlight E-W and N-S trending lineaments indicative of structurally controlled mineralization. High-intensity magnetic anomalies and shallow depth estimates correlate with known mineralized zones, suggesting potential for near-surface barite and base metal deposits. The results emphasize the role of tectonic structures in controlling fluid pathways and mineral deposition. This integrated approach enhances understanding of hydrothermal mineralization processes in the Muri-Lau Sub-Basin and fills an existing knowledge gap on the structural evolution of the area.